New Approach of the Oxidant Peroxo Method (OPM) Route to Obtain Ti(OH)4 Nanoparticles with High Photocatalytic Activity under Visible Radiation - André E. Nogueira; Lucas S. Ribeiro; Luiz F. Gorup; Gelson T. S. T. Silva; Fernando F. B. Silva; Caue Ribeiro; Emerson R. Camargo (International Journal of Photoenergy)
Environmental problems related to the generation of wastewater contaminated with organic compounds and the emissions of pollutants from fuel burning have become major global problems. Thus, there is a need for the development of alternative and economically viable technologies for the remediation of the affected ecosystems. Therefore, this work describes the preparation and characterization of a Ti(OH)4 catalyst with the modified surface for application in the photodegradation of organic compounds (methylene blue (MB) dye and the drug amiloride (AML)) and in the artificial photosynthesis process. Characterization results reveal that peroxo groups on the surface of the catalyst had a great influence on the optical properties of the Ti(OH)4 and consequently in its photocatalytic property. This catalyst showed a high photocatalytic activity for the degradation of organic pollutants under visible radiation, reaching approximately 98% removal of both the dye and the drug in 150 min of reaction. In addition, the catalyst presented a great potential for the reduction of CO2 under ultraviolet (UV) radiation when compared to P25, which is a classic catalyst used in photocatalytic processes. The highest photocatalytic activity can be attributed to the strong visible light absorption, due to the narrow band gap, and the effective separation of photogenerated electron-hole pairs caused by the peroxo groups on the Ti(OH)4 surface.